Reaproveitamento de polifenóis do bagaço de uva através da extração por micro-ondas de hidrodifusão e gravidade seguida de microencapsulação - Moro, Karine Inês Bolson (2021)
Grape pomace corresponds to the main by-product generated in the wine chain, obtained after the pressing of the grapes in the production of white wine and/or after the fermentation step in the red winemaking. It represents a rich source of polyphenols, with physiological effects, directly linked to its technological, antioxidant and antimicrobial properties. Extractive technologies that meet the principles of “green chemistry” have been used to extract polyphenols from agro-industrial residues in an innovative, efficient, economical and environmentally less aggressive way. These techniques have benefits such as reduced extraction time, number of unit operations, energy consumption, environmental impacts, economic costs, quantity of solvents and waste generation. In addition to green extraction methods, microencapsulation technologies are necessary to preserve, make available and ensure the integrity of extracts. Therefore, the objectives of this study were to determine the best extraction condition for grape pomace, using the extractive technology Microwave Hydrodiffusion and Gravity (MHG), aiming yield, phenolic content and antioxidant activity, and to establish storage conditions, functionality and bioactivity for the extract through its entrapment in spray drying. The power of 2 W g-1 in the MHG device was defined as ideal for grape pomace, enabling an efficient extraction due to the high levels of phenolic content and antioxidant activity found in the extracts. Furthermore, significant physicochemical, technological and antioxidant properties were established in the remaining extraction residue, the co-product. Thus, the extract with the best phenolic and antioxidant was microencapsulated. Physicochemical, structural, technological and antioxidant characteristics, including stability of anthocyanin compounds and simulated in vitro gastrointestinal conditions were evaluated. The microcapsules produced showed excellent retention of compounds due to the high encapsulation efficiency obtained and considerable process yield. Structurally, the microcapsules had smooth spherical shapes and no cracks or fissures. Furthermore, the microcapsules showed sensory imperceptible particle size, in addition to slow thermal degradation, contributing to the efficiency of the process. Analysis of the microcapsules by Fourier transform infrared spectroscopy revealed changes in the absorption bands typical of polyphenols. The storage stability study demonstrated that the combinations of carrier agents showed stability of anthocyanic compounds against the storage and protection of anthocyanic compounds in the simulated gastrointestinal system. Therefore, the results found suggest that the association of green extractive technology with the microencapsulation technique enables the obtaining of quality products, with interesting technological and functional characteristics ensuring the sustainability of the wine chain. Thus, being in line with the Objectives of Sustainable Development, the SDGs, of the 2030 Agenda of the UN (United Nations).